The Synchronized Efforts to Decipher the Molecular Basis for Soybean Maturity Loci E1, E2, and E3 That Regulate Flowering and Maturity - Xia, Zhengjun; Zhai, Hong; Wu, Hongyan; Xu, Kun; Watanabe, Satoshi; Harada, Kyuya (Frontiers in Plant Science, 2021)
The general concept of photoperiodism i.e. the photoperiodic induction of flowering was established by Garner and Allard (1920). The genetic factor controlling flowering time, maturity or photoperiodic responses were observed in soybean soon after the discovery of the photoperiodism. The E1, E2, and E3 were named in 1971 and thereafter genetically characterized. At the centennial celebration of the discovery of photoperiodism in soybean, we recount our endeavors to successfully decipher the molecular bases for the major maturity loci E1, E2, and E3 in soybean. Thorough systematic efforts, we successfully cloned E3 gene in 2009, E2 gene in 2011, and E1 gene in 2012. Recently, successful identification of several circadian related genes such as PRR3a, LUX, and J has enriched the known major E1- FTs pathway. Further research progresses on identification of new flowering and maturity related genes as well as coordinated regulation between flowering genes will enable us to understand profoundly flowering gene network and determinants of latitudinal adaptation in soybean.